TRANSFORMING THE INSTITUTION OR INSTITUTIONALIZING THE TRANSFORMATION?: ANTI-RACISM AND EQUITY IN EDUCATION IN TORONTO - Carr, Paul (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1999)
ABSTRACT. This paper reports on the manner in which a large, diverse, urban school board (Toronto, Ontario ) has responded to racial diversity and anti-racist education, and, in a larger sense, equity, from 1970 to 1995. The paper elucidates the factors which characterize the resistance to equity-based institutional change. A qualitative, applied research approach, based on an anti-racist education framework, is used to examine the institutional culture of the board. The research methodology involved interviews and questionnaires with key decision-makers, principals, and teachers. Three key findings are highlighted: 1) the evolutionary nature of attempts to deal with equity issues; 2) the systemic nature of discrimination; and 3) the inability to clearly define anti-racist education and equity, thus impeding the creation of a coherent vision for the implementation of responsive policy initiatives. The discussion focuses on the elements required to facilitate transfonnational change in the institutional culture of the board, emphasizing the concept of accountability. RÉSUMÉ. Cet article rend compte de la façon dont une grande commission scolaire urbaine très diversifiée (Toronto, Ontario) a réagi à la diversité raciale et à l’éducation antiracisme, et dans un sens plus large, à l’équité entre 1970 et 1995. L’article explique les facteurs qui caractérisent la résistance au changement institutionnel fondé sur l’équité. L’auteur utilise une méthode de recherche appliquée et qualitative fondée sur un cadre d’éducation antiracisme pour analyser la culture institutionnelle de la commission scolaire. Cette méthodologie comporte des interviews et des questionnaires avec les grands décideurs, les principaux et les enseignants. Trois grandes constatations s’en dégagent: 1) la nature évolutive des tentatives visant à régler les problèmes d’équité; 2) la nature structurelle de la discrimination; et 3) l’incapacité de définir clairement l’éducation antiracisme et l’équité, ce qui empêche d’avoir une vision cohérente pour prendre des initiatives stratégiques réceptives. L’analyse porte sur les éléments qu’il faut avoir pour faciliter le changement dans la culture institutionnelle de la commission, en soulignant la notion de responsabilisation.